Determinan Konservatisme Akuntansi Pada Perusahaan Real Estate dan Properti - Raha Dewi Neta; Ismunawan Ismunawan (Jurnal Akuntansi Terapan dan Bisnis, 2023)
This study aims to examine the effect of profitability, company size, capital intensity, leverage, and growth opportunities on accounting conservatism in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The objects of this research are companies in the property and real estate sector that are listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. The sampling technique in this study was a purposive sample and the samples used were 30 samples obtained from 10 companies with a three-year observation period 2019-2021. By using data analysis techniques in the form of multiple regression analysis using the SPSS. The results of this study indicate that the variable profitability has a negative effect on accounting conservatism and capital intensity, growth opportunity has an effect on accounting conservatism. Meanwhile, firm size and leverage have no effect on accounting conservatism.